STUDY ON CONSUMER ACCEPTANCE OF OPAQUE CRACKERS WHICH FORTIFIED CATFISH (Pangasius hypopthalmus) PROTEIN CONCENTRATE - Rima Natalina; Dewita Buchari; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to determine the consumer acceptance of opaque crackers which fortified catfish (Pangasius hypothalmus) protein concentrate. The methode used was experimental and complete randomized designed non factorial with 4 level of treatment O0 (without adding catfish protein concentrate), O1 (adding 5% catfish protein concentrate), O2 ( adding 10% catfish protein concentrate), and O3 ( adding 15% catfish protein concentrate). The parameter was observed fororganoleptic test and chemical analysis. The result showed that the adding 5% catfish protein concentrate was most preferable by consumer acceptance by organoleptic test, with criterias: the dominand in catfish protein concentrate flavour and not exessive in seasoning there were no other flavour and not too satly. For chemical analysis: protein content 24.17%, fat content 1.59%, watr content 6.23%, and ash content 4.67%).Keywords : Concentrate Patin, Fortifikasi, Opaque Crackers